Molecular identity of the non-indigenous Cassiopea sp. from Palermo Harbour (central Mediterranean Sea). (11th November 2019) - Maggio, Teresa; Allegra, Alessandro; Bosch-Belmar, Mar; Cillari, Tiziana; Cuttitta, Angela; Falautano, Manuela; Milisenda, Giacomo; Nicosia, Aldo; Perzia, Patrizia; Sinopoli, Mauro; Castriota, Luca
Abstract: The upside-down jellyfish Cassiopea is a benthic scyphozoan, considered a non-indigenous invasive species in the Mediterranean, forming large blooms in eutrophic areas. Taxonomy of the genus Cassiopea is extremely difficult because morphological/meristic characters used are variable within the same species, overlapping among different species, and cryptic species have been identified by molecular markers; nine Cassiopea species are recognized on the basis of molecular study. Mediterranean records of Cassiopea have been ascribed to andromeda species on the basis of a hypothesized invasion pathway from the Suez Canal. In the current study, an analysis of the main morphological characters of the sampled Cassiopea jellyfish from Palermo (Tyrrhenian Sea) was carried out and subsequently, molecular analyses were performed by using COI barcode in order to identify the species. Molecular data were compared with published information in GenBank. Morphological characters were highly variable, but molecular analyses confirmed that Mediterranean Cassiopea specimens belong to andromeda species. Moreover, high values of sequence divergence were found between Mediterranean Cassiopea and the other C. andromeda from the Red Sea, Hawaii and Florida. These results lead to a discussion of possible explanations linked to life history features of the species. Two different explanations are proposed; the first is that Mediterranean C. andromeda, finding a suitable ecological niche good for colonization and proliferation, could have been isolated in Palermo Harbour. The second considers the possibility of multiple introduction events by human transport as demonstrated for other non-indigenous jellyfish; in this case Cassiopea genetic differences increased in the invaded area.